The deficit myth : modern monetary theory and how to build a better economy - Kelton, Stephanie, 1969- (London : John Murray, 2021)
THE INTERNATIONAL BESTSELLER 'Kelton has succeeded in instigating a round of heretical questioning, essential for a post-Covid-19 world, where the pantheon of economic gods will have to be reconfigured' Guardian 'Stephanie Kelton is an indispensable source of moral clarity ... the truths that she teaches about money, debt, and deficits give us the tools we desperately need to build a safe future for all' Naomi Klein 'Game-changing ... Read it!' Mariana Mazzucato 'A rock star in her field' The Times 'This book is going to be influential' Financial Times 'Convincingly overturns conventional wisdom' New York Times Supporting the economy, paying for healthcare, creating new jobs, preventing a climate apocalypse: how can we pay for it all? Leading economic thinker Stephanie Kelton, shows how misguided that question is, and how a radical new approach can maximise our potential as a society. Everything that we've been led to believe about deficits and the role of money and government spending is wrong. Rather than asking the self-defeating question of how to pay for the crucial improvements our society needs, Kelton guides us to ask: which deficits actually matter?
Keywords: Economy